(3GdefgL GdefjQ aj eYQaI CSeGA GdYbGbjQs
(3ChdgG (B:s
(3hHYO aEfi deG QCjJ CSeGA GdYbGbjQ GdWHjI bO OQS QSegG , hJYPQ Ydi GdWdGH YedgG , hde CLO ajgG s
(3BNQgG (B:s
(3hgh ESafL GdHMQ , hgh GdZeGe GdePchQ , dG GdZeGe GdPi Nje HXdI Ydi GdQShd (B((3U(B) s
(3eQJHI Ydi MQha GdgLGA HGUWdGM GdeZGQHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B189 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI(B1079(3g`s
Keywords: (3GdWHs